Promoting University and Industry Links at the Regional Level: Comparing China’s Reform and International Experience - Yang, Po; Cai, Yuzhuo; Lyytinen, Anu; Hölttä, Seppo (Chinese Education & Society, 2016)
This paper intends to learn from international experiences in order to facilitating China's ongoing regional university transformation with an ultimate goal to enhance the role of university in regional economic development and innovation. In so doing, this paper compares major models of universities of applied sciences (UAS) around the world from the perspective of the Triple Helix Model with an emphasis on the nature of university-industry relation implied by each model, and then exploring their relevance for China's UASs transformation. It is concluded that the Finnish model is the most relevant to China. By comparing the Finnish and Chinese practices, a number of recommendations are solicited to Chinese policy-makers.
Keywords: School Business Relationship; Universities; Foreign Countries; Geographic Regions; Educational Change; Comparative Education; Educational Policy; Educational Practices; College Role; Models